A survey of Sternorryncha on tomatoes and potatoes across South Africa with implications for disease vectoring - Zongo, Ayandisa (Rhodes University, 2026)
Pests significantly decrease both the yield and quality of many agricultural crops, ultimately leading to significant economic losses for farmers. Many hemipterans feed on plant sap and affect a wide range of economically important crops. Among these, the most significant phytophagous species are found within the suborder Sternorrhyncha which comprises aphids, psyllids, scales and whiteflies. This group of insects is effective at vectoring plant diseases that lead to production losses. This group of insects is problematic to some of the most important vegetable crops in South Africa, specifically potatoes and tomatoes. Aphids are some of the most important pests of potatoes which can cause damage and yield through direct feeding, but their main impact is due to their ability to transmit viruses such as Potato Leaf Roll Virus (PLRV) and Potato Virus Y (PVY). Whiteflies on the other hand not only suck plant sap but also transmit plant viruses such as Tomato Yellow Leaf Curl Virus (TYLCV), while psyllids spread bacteria such as Candidatus Liberibacter solanacearum. In order to reduce the negative impact of these insect pests, sound pest management strategies have to be implemented. Insect monitoring is a crucial component of integrated pest management (IPM), intended to ensure that pest populations remain below the economic injury level (EIL). Pest surveillance is also essential for assessing the presence and economic impact of pests in agriculture and is carried out to establish the pest status in a given area, enhance the chances of early detection, and track pest prevalence. Therefore, this study aimed to map the prevalence of important aphid species in two different potato producing areas and the impact of environmental factors on aphid species diversity and populations. It also aimed to map the potential outbreaks using a continuous monitoring approach. The study further sought to conduct a survey for incursion by the invasive Bactericera cockerelli Šulc (Hemiptera: Triozidae) as well as the prevalence of other Sternorryncha on Solanaceae plants in South Africa, establishing whether B. cockerelli or other non-native psyllids are present in the surveyed regions. This surveillance is intended to inform future biosecurity measures and contribute to South Africa’s preparedness against high-risk agricultural pests. A continuous monitoring approach across multiple growing seasons was carried out in two potato growing regions of South Africa, Christiana, North-West and Douglas, Northern Cape to collect aphid populations using suction traps. A field national survey using sticky traps, bucket traps and physical sampling was also carried to monitor Sternorryncha of interest on solanaceae in South Africa over 2 years. Collected insects were preserved in alcohol and identified to species or genus level using dichotomous identification keys. Furthermore, DNA extractions and sequencing were done on the aphid specimens to confirm the morphological identifications. For the continuous monitoring survey, 39 species were collected with, Acyrthosiphon kondoi Shinji (Hemiptera: Aphididae), Aphis spp Linnaeus (Hemiptera: Aphididae), Metopolophium dirhodum Walker (Hemiptera: Aphididae), Pemphigus spp Hartig (Hemiptera: Aphidoidea, Eriosomatidae), Rhopalosiphum maidis Fitch (Hemiptera: Aphididae), Rhopalosiphum padi Linnaeus (Hemiptera: Aphididae) and Therioaphis trifolii Monell (Hemiptera: Aphididae) recorded as the most abundant species that potentially vector the important potato viruses, PVY and PLRV. Rhopalosiphum padi and Rhopalosiphum maidis were the most abundant potential PVY vectors while Myzus persicae Sulzer (Hemiptera: Aphididae) was the most abundant potential vector for PLRV. The aphid populations were mostly influenced by temperature (both monthly averages of daily maximum and minimum), windspeed and precipitation where an increase in temperature led to an increase in aphid populations. Temperature data were recorded daily and averaged over each month for the analysis. The diversity, evenness and abundance of aphid species collected was similar across the sampling locations. For the national survey, with targeted surveillance for the invasive B. cockerelli, a total of 49 aphid species, 37 psyllid species and 1 whitefly species and other non-sternorryncha (Diptera, Hymenoptera, Thysanoptera, Nueroptera, Mantidae, Coleoptera, Lepidoptera and Hemiptera) were collected. Out of the three collection methods used to collect insects, sticky traps captured a lot more psyllid species while bucket traps captured more aphid species and outperformed the other methods used. The most abundant aphid species were, R. maidis, Aphis spp and R. padi; while the tipu psyllid, Platycorypha nigrivirga Burckhardt (Hemiptera: Psylloidea) was the most dominant psyllid species. The whitefly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) was most abundant on the tomato crops compared to the other crops sampled. There were no psyllid species associated with solanaceous crops collected in the field and all the sampled plants did not host B. cockerelli, however, its congeneric species Bactericera capensis Hollis, 1984 was collected during sampling hosted by non-crop solanaceae. The diversity, evenness and abundance of the Sternorryncha insects collected was also similar across the sampling locations. The findings indicate that there was a high diversity of Sternorryncha that feed on solanaceous crops, potentially spreading viruses with temperature influencing these populations. Furthermore, agricultural crops may harbour insects not associated with them. Additionally, B. cockerelli was not encountered during the field work even though B. capensis was collected, indicating that South Africa is still safe from the invasive pest. Thus, constant monitoring should remain active in order to detect its incursion into the country. Further studies into the biology and distribution of B. capensis need to be conducted in order to compare it with B. cockerelli. This will help researchers understand whether these two species would have a synergistic effect to each other should there be an incursion into the country. Furthermore, it will be worthwhile to test B. capensis and its wild hosts for any Liberibacter that might potentially be spread by B. cockerelli should there be incursion.
Keywords: Sternorrhyncha (https://www.wikidata.org/wiki/Q621840); Potatoes -- Diseases and pests (http://id.loc.gov/authorities/subjects/sh85105656); Tomatoes -- Diseases and pests (http://id.loc.gov/authorities/subjects/sh85135926); Bactericera cockerelli (https://www.wikidata.org/wiki/Q3410223); Entomology